Ultrasonographic features of dysgerminoma, apropos of 3 cases - Lacunza Paredes, Rommel Omar (2024)
Ovarian germ cell tumors are a very diverse histologic group. The most frequentmalignant tumor of this lineage is dysgerminoma, which mainly affects youngwomen. There are few reports on the particular characteristics on ultrasound, beingincluded dysgerminoma indistinctly in series of ovarian tumors as a solid mass.Computed tomography and magnetic resonance have contributed significantlyto the characterization of dysgerminoma. The following is a description of threecases of dysgerminomas suspected by ultrasound, in order to determine commoncharacteristics and contrast them with the findings in the literature.